L’internet : un nouvel outil pour de nouvelles pratiques de documentation pour la préparation de classe ? - Philippe Charpentier (Recherches en Éducation)
The scholar’s handbook had been used for a long time as the main support by the teachers of primary school in France to prepare the lessons. However, since recently, the teachers can use the internet which permits the access to informations, documentation to prepare their lessons. This is from the particular case of the subject of geography at the Cycle 3 of the french primary school and from a survey by questionnaire that we try to weigh up the impact of the internet for the preparation of the lessons. From that survey, we can say that the scholar handbook remains the main tool used by the teachers to prepare lessons; the use of the internet is for the moment only a complement of this last one. Moreover, the teachers fell alone in front of the documents they find by lack of both initial and continue formation.